Design and optimization of yokeless magnetic gear with asymmetric Halbach permanent magnet array for electric vehicle powertrain - Yuanxi Chen; Xing Zhao; Siulau Ho; Shuangxia Niu; Weinong Fu (IET Renewable Power Generation, 2022)
Abstract In this paper, a novel 3/27/24 (pole pairs of inner rotor permanent magnet [PM]s/modulator/outer rotor PMs) high torque density yokeless magnetic gear with asymmetric Halbach PM array is presented and optimized for electric vehicle powertrain. The key is to improve the torque performance by replacing the magnetic steel with the light nonmagnetic material as the rotor core and employing the embedded magnetic steel bar as well as trapezoidal PM structure to form a low magnetic resistance in the magnetic circuit. The proposed machine has significant performance improvements in two aspects. Firstly, it has high torque density and low iron loss with the yokeless structure. Secondly, it has a high anti‐saturation capability and low torque ripple with the asymmetric Halbach PM array and the embedded magnetic steel bar. The proposed structure is optimized by the co‐simulation of the finite‐element method and C++ optimization software. For a clear evaluation, the proposed structure is compared with generalized solutions in terms of performance and cost. Comparison results indicate that the proposed solution has the highest output torque, torque density, and torque per PM weight among solutions, reaching 214.1 N·m, 58.2 N·m/kg, and 95.6 N·m/kg, which greatly enhances the performance of the magnetic gear.